Allergic rhinitis - a review on recent advances in characteristics, diagnostic and treatments - Lisowska, Aleksandra; Żaba, Ziemwowit; Żołyniak, Wojciech; Warzyszak, Paweł; Milczek, Maria; Małek, Róża; Hawranik, Izabela; Tomasik, Mikołaj; Niski, Szymon; Skrzypek, Mateusz (Journal of Education, Health and Sport, 2022)
Introduction: Allergic rhinitis is an inflammation of the nasal mucosa characterized by nasal discharge or down the back of the throat, sneezing, stuffy or itchy nose. Allergic rhinitis can be caused by various allergens - pollen, house dust mites, animal allergens, fungi. It can occur periodically or chronically, as a year-round allergic rhinitis. Allergic rhinitis (AR) is a common condition, epidemiological studies suggest that it affects 20–30% of adults and up to 40% of children. Objective: The purpose of this review is to analyze the latest information on the characteristics, diagnosis and treatment of patients with allergic rhinitis. Material and metods: This review was based on available data collected in the PubMed data base. The research was done by looking through key words such as: “allergic rhinitis”, “Local nasal allergy”, “diagnosis” and “treatment”. State of knowledge: The main challenges with allergic rhinitis relate to its treatment. Symptomatic and anti-inflammatory drugs are often used and are not fully effective. The diagnosis of allergic rhinitis can be diagnosed by history and physical examination, with testing reserved for treatment of nonresponders. Summary: Treatment should be comprehensive and take into account the environment, pharmacotherapy, allergen immunotherapy, if indicated. As a disease that affects many people and significantly reduces the quality of life, allergic rhinitis deserves a thorough understanding of its symptoms, diagnosis and treatment.